An Investigation into the Possibilities of BIM and GIS Cooperation and Utilization of GIS in the BIM Process - Pavel Tobiáš (Geoinformatics FCE CTU, 2015)
In the coming years we will most probably watch a significant increase of the BIM (building information model) utilization in the AEC (Architecture/Engineering/Construction) sector even in the Czech Republic. Therefore, it would be reasonable to consider possible utilization of the well-established geographic information systems within the building information modelling process. This paper is based on the currently existing literature and is focused on the interrelationship between BIM and GIS. The main goal is to reveal potential fields of cooperation and to find possible utilization of GIS in BIM. To provide a theoretical framework, this article briefly introduces and defines the term of BIM and deals with the most important semantic models in AEC and 3D GIS IFC and CityGML. The paper also contains examples of specific efforts recently dealing with the BIM and GIS collaboration.